RANCANG BANGUN TESLA COIL GUN PEMANCAR TRANSFER DAYA LISTRIK TEGANGAN TINGGI NIRKABEL DENGAN BEBAN LAMPU - Nanda Nugraha Utama, I Putu; Arta Wijaya, I Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i03.p3, 2021)
Media in the distribution of electrical energy is still using wired until now, in the future cable may be abandoned and switch to wireless. The scientist of Nikola Tesla creat the Tesla coil which will become the forerunner of wireless electricity distribution that can turn on lights by means of air. The purpose of this study to determine the effect of distance on voltage, current, power, electromagnetic induction emitted and the flux of light. The method of analysis uses calculations, tests and measurements obtained from primary data. In general, the data used in this thesis are the input voltage 5 V and current 1 A, the voltage result by the high voltage generator was 400 kV, the number of secondary windings was 1400 coils, the number of primary turns was 10 coils, the pipe diameter was 3.81 cm. The diameter of the torus was 8 cm, the distance of the spark gap was 1 cm, the lamps used were TL 8 W, 5 W, LED 5 W and incandescent lamp 5 W, the test used variations in the distance of 1 cm, 3 cm, 5 cm, 7 cm, 9 cm and 11 cm from transmitter to load. From all the tests carried out with distance variations to voltage, elektromagnetic induction and flux, it was found that distance greatly with TL 8 W affected the voltage was 0.2 V, electromagnetic induction was 22859,2 x 10-7 Tesla and light flux emitted by the lamp was 4.8 x 10-4 Lumen. If the radius or distance of the transmitter was got closer, the value could receive get bigger and the farther the value could get smaller.